A method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics

By doping (Li0.5Bi0.5)2+ composite ion doping on MgGa2O4 microwave dielectric ceramics and forming a sintering atmosphere using BaCu (B2O5) and LiF mixture, the sintering temperature of magnesium gallate ceramics was successfully reduced and the sintering temperature was solved The high and high dielectric loss problem has achieved efficient preparation of microwave dielectric ceramic materials.

CN119118630BActive Publication Date: 2025-02-07SHANDONG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411616564.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-07
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The sintering temperature of spinel structure magnesium gallate is too high, which is difficult to meet the needs of low-temperature co-fired ceramic technology. In addition, traditional methods reduce the sintering temperature will increase the dielectric loss of the material, limiting its application in the field of microwave communication.

Method used

MgGa2O4 is doped with A-position of (Li0.5Bi0.5)2+ composite ions, and a mixture of BaCu (B2O5) and LiF are laid in the alumina calcining crucible to form a sintering atmosphere, and the sintering temperature is from 1400°C or above. Reduced to 1000~1250℃.

Benefits of technology

It realizes the sintering temperature of MgGa2O4 microwave dielectric ceramics, while maintaining high quality factor and low dielectric constant, and is suitable for microwave communication field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118630B_ABST
    Figure CN119118630B_ABST
Patent Text Reader

Abstract

The present application provides a method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics, the method comprising two steps: (1) using (Li 0.5 Bi 0.5 ) 2+ The composite ions are doped at the A position of MgGa2O4, (2) a mixture of BaCu(B2O5) and LiF is placed in an alumina crucible, and sintered at 1000-1250°C to form a sintering atmosphere. The above method can reduce the sintering temperature of MgGa2O4 microwave dielectric ceramics from the traditional 1400°C to 1000-1250°C. The relative density of MgGa2O4 microwave dielectric ceramics prepared by this method is greater than 95%, and the material dielectric constant is measured to be 6.5-9.5 at a frequency of 14-16 GHz; the Q×f value is 60000-130000GHz; and the resonant frequency temperature coefficient is ‑78-‑10ppm / °C. The method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics is expected to become a key preparation process in the fields of new generation electronic communications, green processing, environmental protection, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electronic information functional materials and integrated circuits, and in particular to a method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics. Background Art

[0002] With the rapid development of the new generation of wireless communications, the Internet of Everything, and new energy vehicles, high-frequency microwave communication technology plays a vital role in the global society. In the field of microwave communications, electronic components and various functional modules play an important role. With the sharp reduction in equipment size and weight in recent years, the miniaturization and multifunctional integration of components have become the core driving force of communication technology. Microwave dielectric ceramics are the core components of passive devices in 5G communications. Low-dielectric microwave dielectric ceramics are often used as substrate materials for microwave devices to reduce signal attenuation and distortion.

[0003] Spinel structure magnesium gallate has a low dielectric constant and a high quality factor, but its sintering temperature is too high (>1400℃), which makes it difficult to meet the technical requirements of low-temperature co-fired ceramics and is not conducive to energy conservation and environmental protection. Traditional methods usually add low softening point glass or low melting point oxides to magnesium gallate ceramics to reduce the sintering temperature, but this will greatly increase the dielectric loss of the material and limit its application in the field of microwave communications. Therefore, it is urgent to develop new methods to reduce the sintering temperature of magnesium gallate microwave dielectric ceramic materials. Summary of the invention

[0004] The present application provides a method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics, aiming to reduce the sintering temperature of magnesium gallate ceramics while having a high quality factor and a low dielectric constant.

[0005] A method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics, characterized by comprising the following steps:

[0006] (1) Adopt (Li 0.5 Bi 0.5 ) 2+ The composite ions dope MgGa2O4 at the A position, wherein (Li 0.5 Bi 0.5 ) 2+ The doping amount of the composite ion is 0~0.08 mol, and the chemical formula is (Li 0.5 Bi 0.5 ) x Mg 1-x Ga2O4( x =0~0.08)

[0007] (2) Place a mixture of BaCu(B2O5) and LiF in an alumina crucible and sinter at 1000-1250°C to form a sintering atmosphere;

[0008] The above method can reduce the sintering temperature of MgGa2O4 microwave dielectric ceramics from the traditional 1400°C to 1000~1250°C.

[0009] The present application provides a method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics, characterized in that (Li 0.5 Bi 0.5 ) 2+ The specific steps of A-site doping of MgGa2O4 with composite ions are as follows:

[0010] (1) According to (Li 0.5 Bi 0.5 ) x Mg 1-x Ga2O4( x =0~0.08) weigh Li2CO3, Bi2O3, MgO, Ga2O3 raw materials, the purity of each raw material is greater than 99.0%;

[0011] (2) ball-milling the raw material mixture of step (1) in anhydrous ethanol medium, grinding after drying, passing through a 100-mesh sieve, and pre-calcining at 1000-1150° C. for 4 h at a heating rate of 3-5° C. / min, cooling naturally to room temperature, and then grinding to obtain a pre-calcined powder;

[0012] (3) The pre-calcined powder and the polyvinyl alcohol (PVA) binder in a mass ratio of 1:(15-20) were mixed in an agate mortar and granulated uniformly;

[0013] (4) Dry-press the granulated powder under a pressure of 100-200 MPa for 1-2 minutes;

[0014] (5) The dry-pressed ceramic green body is kept at 500-600°C for 4-8 h for debinding treatment at a heating rate of 1-2°C / min to obtain a sample to be fired.

[0015] The present application provides a method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics, characterized in that the formation of the sintering atmosphere specifically includes the following steps:

[0016] (1) BaCO3, CuO and H3BO3 raw materials required for preparing BaCu(B2O5) are weighed according to the stoichiometric ratio, and the purity of each raw material is greater than 99.0%;

[0017] (2) ball milling the raw material of step (1) in anhydrous ethanol medium, grinding after drying, passing through a 100 mesh sieve, pre-calcining at 800-850°C for 4 h at a heating rate of 3-5°C / min, cooling naturally to room temperature and grinding to obtain BaCu(B2O5) powder;

[0018] (3) Mixing BaCu(B2O5) powder and LiF in a mass ratio of (7-3):(3-7), grinding them thoroughly to obtain a dry and uniform powder;

[0019] (4) Arrange in the alumina crucible in the following order:

[0020] Bottom layer: pad with zirconium oxide dry powder, thickness 2~3mm;

[0021] Middle layer: BaCu(B2O5) and LiF mixed powder, thickness 0.2~0.5mm;

[0022] Top layer: zirconium oxide dry powder, thickness 0.2~0.5mm;

[0023] The mass ratio of powder in the three layers is (6~8):(2~1):(2~1);

[0024] (5) The sample to be sintered is placed in the alumina crucible prepared in step (4) for sintering at a temperature of 1000-1250°C, a heating rate of 3-5°C / min, and a holding time of 4-8h. The sample is cooled to room temperature to obtain a sintered dense MgGa2O4 microwave dielectric ceramic.

[0025] Preferably, the wet ball milling media described in steps

[0006] and

[0007] are anhydrous ethanol and zirconium oxide balls, the mass ratio of the raw material to the zirconium oxide balls in the grinding jar is (4-6):1, the ball milling time is 8-10 hours, the ball milling speed is 200-300 r / min; the mixed material drying temperature is 50-80°C, and the time is 12-20 hours.

[0026] The MgGa2O4 microwave dielectric ceramic prepared by a method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramic provided in the present application has a relative density after sintering greater than 95%, a material dielectric constant of 6.5 to 9.5 measured at a frequency of 14 to 16 GHz, a Q×f value of 60,000 to 130,000 GHz, and a resonant frequency temperature coefficient of -78 to -10 ppm / °C.

[0027] Spinel structure magnesium gallate has excellent dielectric properties, but due to its strong chemical bond structure, its sintering temperature is relatively high. Usually, low melting point glass or oxide is added to reduce its sintering temperature, but it will also greatly deteriorate its dielectric loss. The microwave dielectric ceramic material prepared by a method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramic provided in the present application has excellent sintering performance and dielectric properties. The sintering temperature is reduced by ion doping modification and sintering atmosphere assisted sintering, and has good dielectric properties. By adjusting Li + 、Bi 3+By adjusting the ion doping ratio, the dielectric constant of the ceramic can be varied between 6.5 and 9.5, with a maximum Q×f value of 130,000 GHz. It is expected to become a key basic material for the manufacture of integrated circuit substrates, RF components and electronic packaging equipment.

[0028] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.

[0029] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each embodiment, enumeration is only used as a representative group and should not be interpreted as exhaustive. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Attached Figure 1 This is the XRD diagram of the MgGa2O4 microwave dielectric ceramic prepared in Example 1.

[0031] Attached Figure 2 This is a sintering flow chart of the MgGa2O4 microwave dielectric ceramics prepared in Examples 1, 2, and 3.

[0032] Attached Figure 3 This is the SEM image of the MgGa2O4 microwave dielectric ceramic prepared in Example 1.

[0033] Attached Figure 4 This is the SEM image of the MgGa2O4 microwave dielectric ceramic prepared in Example 2.

[0034] Attached Figure 5 This is the SEM image of the MgGa2O4 microwave dielectric ceramic prepared in Example 3. DETAILED DESCRIPTION

[0035] Example

[0036] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application will be apparent to those skilled in the art. All reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0037] Example 1

[0038] The steps of preparing the microwave dielectric ceramic in this embodiment are as follows:

[0039] (1) Weigh 0.00025 mol Li2CO3, 0.00025 mol Bi2O3, 0.05 mol Ga2O3, and 0.049 mol MgO in proportion and perform wet ball milling with a ball-to-material ratio of 4:1 and a ball milling time of 8 h; after mixing, dry in an oven at 50°C for 20 h to obtain a dry raw material;

[0040] (2) Pre-calcining the dry powder obtained in step (1) at 1150°C for 4 hours. Then, the pre-calcined powder is mixed with anhydrous ethanol and fully ball-milled at a ball-to-powder ratio of 4:1 for 8 hours. After ball-milling, the powder is dried in an oven at 50°C for 20 hours to obtain a pre-calcined powder;

[0041] (3) Adding polyvinyl alcohol (PVA) binder to the dry powder obtained in step (2), PVA: preformed powder = 1:17, mixing and granulating in an agate mortar to obtain a preformed powder with good fluidity;

[0042] (4) The prefabricated powder obtained in step (3) is pressed by dry pressing at a pressure of 100 MPa for 1 min, and the formed ceramic green body is kept at 500° C. for 8 h for debinding;

[0043] (5) Weigh 0.1 mol BaCO3, 0.1 mol CuO, and 0.2 mol H3BO3 in proportion and perform wet ball milling with a ball-to-material ratio of 4:1 for 8 h; after mixing, dry in an oven at 50°C for 20 h to obtain a dry raw material;

[0044] (6) Pre-calcining the dried powder obtained in step (5) at 825°C for 3 hours. Then, the pre-calcined powder is mixed with anhydrous ethanol and fully ball-milled at a ball-to-powder ratio of 4:1 for 8 hours. After ball-milling, it is dried in an oven at 50°C for 20 hours to obtain pre-calcined BaCu(B2O5) powder;

[0045] (7) Grinding and mixing the BaCu(B2O5) and LiF described in step (6) at a mass ratio of 5:5 to obtain a dry and uniform powder;

[0046] (8) Arrange in the alumina crucible in the following order:

[0047] Bottom layer: pad with zirconium oxide dry powder, thickness 2mm;

[0048] Middle layer: BaCu(B2O5) and LiF mixed powder, thickness 0.3mm;

[0049] Top layer: zirconium oxide dry powder, thickness 0.3mm;

[0050] The mass ratio of powder in the three layers is 8:1:1;

[0051] (9) The ceramic green body is placed in the alumina crucible in step (8) and sintered at 1250° C. with a heating rate of 5° C. / min and a holding time of 4 h to obtain a magnesium gallate-based microwave dielectric ceramic.

[0052] Attached Figure 1 The XRD image of the microwave dielectric ceramics obtained shows that no other impurities are generated except the magnesium gallate phase. Figure 2 The following is the flow chart corresponding to the above step (8), showing the specific process content of setting the combustion-supporting atmosphere. Figure 3 This is a SEM image of the ceramic. It can be seen from the figure that the ceramic has high density, few pores, and a relative density of 99.2%. Its dielectric constant is 9.41 at 14.7GHz, and the Q×f value is 127159 GHz; the resonant frequency temperature coefficient is -39.6 ppm / ℃.

[0053] Example 2

[0054] The steps of preparing the microwave dielectric ceramic in this embodiment are as follows:

[0055] (1) Weigh 0.0005 mol Li2CO3, 0.0005 mol Bi2O3, 0.05 mol Ga2O3, and 0.048 mol MgO in proportion and perform wet ball milling with a ball-to-material ratio of 4:1 and a ball milling time of 9 h; after mixing, dry in an oven at 70°C for 15 h to obtain a dry raw material;

[0056] (2) Pre-calcining the dry powder obtained in step (1) at 1150°C for 5 hours. Then, the pre-calcined powder is mixed with anhydrous ethanol and fully ball-milled at a ball-to-powder ratio of 5:1 and a ball-milling time of 9 hours. After ball-milling, the powder is dried in an oven at 70°C for 15 hours to obtain a pre-calcined powder;

[0057] (3) Adding polyvinyl alcohol (PVA) binder to the dry powder obtained in step (2), PVA: prefabricated powder = 1:15, mixing and granulating in an agate mortar to obtain a prefabricated powder with good fluidity;

[0058] (4) The prefabricated powder obtained in step (3) is pressed by dry pressing at a pressure of 100 MPa for 2 min, and the formed ceramic green body is kept at 550° C. for 6 h for debinding;

[0059] (5) Weigh 0.1 mol BaCO3, 0.1 mol CuO, and 0.2 mol H3BO3 in proportion and perform wet ball milling with a ball-to-material ratio of 4:1 for 8 h; after mixing, dry in an oven at 70°C for 15 h to obtain a dry raw material;

[0060] (6) Pre-calcine the dry powder obtained in step (5) at 825°C for 3 hours. Then, mix the pre-calculated powder into anhydrous ethanol and fully ball-mill it at a ball-to-powder ratio of 4:1 for 8 hours. After ball-milling, dry it in an oven at 70°C for 15 hours to obtain pre-calculated BaCu(B2O5) powder;

[0061] (7) Grinding and mixing the BaCu(B2O5) and LiF described in step (6) in a mass ratio of 6:4 to obtain a dry and uniform powder;

[0062] (8) Arrange in the alumina crucible in the following order:

[0063] Bottom layer: pad with zirconium oxide dry powder, thickness 2.5mm;

[0064] Middle layer: BaCu(B2O5) and LiF mixed powder, thickness 0.4mm;

[0065] Top layer: zirconium oxide dry powder, thickness 0.4mm;

[0066] The mass ratio of powder in the three layers is 6:2:2;

[0067] (9) The ceramic green body is placed in the alumina crucible in step (8) and sintered at 1250° C. with a heating rate of 5° C. / min and a holding time of 6 h to obtain a magnesium gallate-based microwave dielectric ceramic.

[0068] The XRD image of the ceramic is shown in the attached Figure 1 Similarly, it can be seen from the figure that except for the magnesium gallate phase, no other impurity phase is generated. Figure 2 The following is the flow chart corresponding to the above step (8), showing the specific process content of setting the combustion-supporting atmosphere. Figure 4 This is a SEM image of the ceramic. It can be seen from the figure that the ceramic has high density, few pores, and a relative density of 98.9%. Its dielectric constant is 9.39 and the Q×f value is 99560GHz at 15GHz; the temperature coefficient of the resonant frequency is -49.8 ppm / ℃.

[0069] Example 3

[0070] The steps of preparing the microwave dielectric ceramic in this embodiment are as follows:

[0071] (1) Weigh 0.00075 mol Li2CO3, 0.00075 mol Bi2O3, 0.05 mol Ga2O3, and 0.047 mol MgO in proportion and perform wet ball milling with a ball-to-material ratio of 6:1 and a ball milling time of 8 h; after mixing, dry in an oven at 80°C for 10 h to obtain a dry raw material;

[0072] (2) Pre-calcining the dry powder obtained in step (1) at 1150°C for 4 hours. Then, the pre-calcined powder is mixed with anhydrous ethanol and fully ball-milled at a ball-to-powder ratio of 6:1 and a ball-milling time of 8 hours. After ball-milling, the powder is dried in an oven at 80°C for 10 hours to obtain a pre-calcined powder;

[0073] (3) Adding polyvinyl alcohol (PVA) binder to the dry powder obtained in step (2), PVA: preformed powder = 1:20, mixing and granulating in an agate mortar to obtain a preformed powder with good fluidity;

[0074] (4) The prefabricated powder obtained in step (3) is pressed by dry pressing at a pressure of 150 MPa for 1.5 min, and the formed ceramic green body is kept at 550° C. for 6 h for debinding;

[0075] (5) Weigh 0.1 mol BaCO3, 0.1 mol CuO, and 0.2 mol H3BO3 in proportion and perform wet ball milling with a ball-to-material ratio of 4:1 for 8 h; after mixing, dry in an oven at 70°C for 15 h to obtain a dry raw material;

[0076] (6) Pre-calcine the dry powder obtained in step (5) at 825°C for 3 hours. Then, mix the pre-calculated powder into anhydrous ethanol and fully ball-mill it at a ball-to-powder ratio of 4:1 for 8 hours. After ball-milling, dry it in an oven at 70°C for 15 hours to obtain pre-calculated BaCu(B2O5) powder;

[0077] (7) Grinding and mixing the BaCu(B2O5) and LiF described in step (6) in a mass ratio of 4:6 to obtain a dry and uniform powder;

[0078] (8) Arrange in the alumina crucible in the following order:

[0079] Bottom layer: pad with zirconium oxide dry powder, thickness 3mm;

[0080] Middle layer: BaCu(B2O5) and LiF mixed powder, thickness 0.3mm;

[0081] Top layer: zirconium oxide dry powder, thickness 0.3mm;

[0082] The mass ratio of powder in the three layers is 7:2:1;

[0083] (9) The ceramic green body is placed in the alumina crucible in step (8) and sintered at 1250° C. with a heating rate of 5° C. / min and a holding time of 6 h to obtain a magnesium gallate-based microwave dielectric ceramic.

[0084] The XRD image of the ceramic is shown in the attached Figure 1Similarly, it can be seen from the figure that except for the magnesium gallate phase, no other impurity phase is generated. Figure 2 The following is the flow chart corresponding to the above step (8), showing the specific process content of setting the combustion-supporting atmosphere. Figure 5 This is a SEM image of the ceramic. It can be seen from the figure that the ceramic has high density, few pores, and a relative density of 97.8%. Its dielectric constant is 9.31 at 14.3GHz, and the Q×f value is 86230GHz; the resonant frequency temperature coefficient is -60.8 ppm / ℃.

[0085] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics, characterized by comprising the following steps: (1) Adopt (Li 0.5 Bi 0.5 ) 2+ The composite ions dope MgGa2O4 at the A position, wherein (Li 0.5 Bi 0.5 ) 2+ The doping amount of the composite ion is less than or equal to 0.08 mol, and the chemical formula is (Li 0.5 Bi 0.5 ) x Mg 1-x Ga2O4 (x≤0.08) materials, the (Li 0.5 Bi 0.5 ) 2+ The doping amount of the composite ions is not zero and the value of x is not zero; (2) Place a mixture of BaCu(B2O5) and LiF in an alumina crucible and sinter at 1000-1250°C to form a sintering atmosphere; The above method can reduce the sintering temperature of MgGa2O4 microwave dielectric ceramics from the traditional 1400°C to 1000~1250°C.

2. A method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics according to claim 1, characterized in that: Adopt (Li 0.5 Bi 0.5 ) 2+ The specific steps of A-site doping of MgGa2O4 with composite ions are as follows: (1) According to (Li 0.5 Bi 0.5 ) x Mg 1-x Ga2O4( x =0~0.08) weigh Li2CO3, Bi2O3, MgO, Ga2O3 raw materials, the purity of each raw material is greater than 99.0%; (2) ball-milling the raw material mixture of step (1) in anhydrous ethanol medium, grinding after drying, passing through a 100-mesh sieve, and pre-calcining at 1000-1150° C. for 4 h at a heating rate of 3-5° C. / min, cooling naturally to room temperature, and then grinding to obtain a pre-calcined powder; (3) The pre-calcined powder and the polyvinyl alcohol (PVA) binder in a mass ratio of 1: (15-20) were mixed in an agate mortar and granulated uniformly; (4) Dry-press the granulated powder under a pressure of 100-200 MPa for 1-2 minutes; (5) The dry-pressed ceramic green body is kept at 500-600°C for 4-8 h for debinding treatment at a heating rate of 1-2°C / min to obtain a sample to be fired.

3. The method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics according to claim 1, characterized in that: The forming of the combustion-supporting atmosphere specifically comprises the following steps: (1) BaCO3, CuO and H3BO3 raw materials required for preparing BaCu(B2O5) are weighed according to the stoichiometric ratio, and the purity of each raw material is greater than 99.0%; (2) ball milling the raw material of step (1) in anhydrous ethanol medium, grinding after drying, passing through a 100 mesh sieve, pre-calcining at 800-850°C for 4 h at a heating rate of 3-5°C / min, cooling naturally to room temperature and grinding to obtain BaCu(B2O5) powder; (3) Mixing BaCu(B2O5) powder and LiF in a mass ratio of (7-3):(3-7), grinding them thoroughly to obtain a dry and uniform powder; (4) Arrange in the alumina crucible in the following order: Bottom layer: pad with zirconium oxide dry powder, thickness 2~3mm; Middle layer: BaCu(B2O5) and LiF mixed powder, thickness 0.2~0.5mm; Top layer: zirconium oxide dry powder, thickness 0.2~0.5mm; The mass ratio of powder in the three layers is (6~8):(2~1):(2~1); (5) The sample to be sintered is placed in the alumina crucible prepared in step (4) for sintering at a temperature of 1000-1250°C, a heating rate of 3-5°C / min, and a holding time of 4-8h. The sample is cooled to room temperature to obtain a sintered dense MgGa2O4 microwave dielectric ceramic.

4. The method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics according to claim 2, characterized in that The ball milling media described in step (2) are anhydrous ethanol and zirconium oxide balls. The mass ratio of the raw materials to the zirconium oxide balls in the grinding jar is (4-6):

1. The ball milling time is 8-10 hours, and the ball milling speed is 200-300 r / min. The drying temperature of the mixture is 50-80°C, and the drying time is 12-20 hours.

5. The method for reducing the sintering temperature of MgGa2O4 microwave dielectric ceramics according to claim 3, characterized in that The ball milling media described in step (2) are anhydrous ethanol and zirconium oxide balls. The mass ratio of the raw materials to the zirconium oxide balls in the grinding jar is (4-6):

1. The ball milling time is 8-10 hours, and the ball milling speed is 200-300 r / min. The drying temperature of the mixture is 50-80°C, and the drying time is 12-20 hours.

6. The MgGa2O4 microwave dielectric ceramic prepared by the method according to claim 1, characterized in that The relative density is greater than 95%. The dielectric constant of the material is measured to be 6.5 to 9.5 at a frequency of 14 to 16 GHz. The Q×f value is 60,000 to 130,000 GHz. The temperature coefficient of the resonant frequency is -78 to -10 ppm / °C.

Citation Information

Patent Citations

  • BaCu(B2O5)-doped multiphase microwave dielectric ceramic and preparation method thereof

    CN107867851A

  • Novel low-temperature co-fired ceramic material and preparation method thereof

    CN116041062A